2022
DOI: 10.3390/cancers14122916
|View full text |Cite
|
Sign up to set email alerts
|

StarDist Image Segmentation Improves Circulating Tumor Cell Detection

Abstract: After a CellSearch-processed circulating tumor cell (CTC) sample is imaged, a segmentation algorithm selects nucleic acid positive (DAPI+), cytokeratin-phycoerythrin expressing (CK-PE+) events for further review by an operator. Failures in this segmentation can result in missed CTCs. The CellSearch segmentation algorithm was not designed to handle samples with high cell density, such as diagnostic leukapheresis (DLA) samples. Here, we evaluate deep-learning-based segmentation method StarDist as an alternative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…In a large multicenter international study for BrCa CTC detection, a higher inter-reader variability was found in the early cancer setting, where a small number of CTCs was detected . Semiautomated CTC detection could be considerably improved by new image processing tools, such as deep-learning-based segmentation algorithms . Preanalytical variables (e.g., blood collection tubes, sample collection and handling, processing time, etc.)…”
Section: Challenges and Perspectives In Ctc Analyses For Medical Diag...mentioning
confidence: 99%
“…In a large multicenter international study for BrCa CTC detection, a higher inter-reader variability was found in the early cancer setting, where a small number of CTCs was detected . Semiautomated CTC detection could be considerably improved by new image processing tools, such as deep-learning-based segmentation algorithms . Preanalytical variables (e.g., blood collection tubes, sample collection and handling, processing time, etc.)…”
Section: Challenges and Perspectives In Ctc Analyses For Medical Diag...mentioning
confidence: 99%
“…For each cell, mean protein intensity signal was measured and assigned into the cell protein expression level. After several signal preprocessing steps to normalise and remove outlier signal, a standard cell type clustering was applied using a common single-cell processing pipeline, scanpy (33,45).…”
Section: Phenoimager Ht Cell Type and Cell Community Analysismentioning
confidence: 99%
“…As such, poor single cell segmentation can have dramatic and confounding effects on accurate cell type/state identification, akin to measuring doublets/aggregates of debris by conventional flow cytometry or scRNAseq. There are a number of published "end to end" pipelines for IMC data analysis (8)(9)(10)(11)(12) that utilise open source software for segmentation such as Ilastik (13) and CellProfiler (14,15), as well as StarDist (16) and IMC-specific approaches that utilise deep learning (17). There have also been attempts to use matched fluorescent images of the nuclei using DAPI co-staining to improve segmentation accuracy (18) as well as removing image noise (19,20).…”
Section: Introductionmentioning
confidence: 99%